DAMPAK KOMPETENSI PROFESIONAL GURU DALAM MENINGKATKAN MUTU PENDIDIKAN MADRASAH IBTIDAIYAH DI KOTA SALATIGA - Nur Hasanah (State Institute of Islamic Studies (IAIN) Salatiga, 2015)
This study aimed to determine the professional competence of teachers in Islamic Elementary School, factors that influence professional competence, and the impact of professional competence of teachers in improving the quality of education in Islamic Elementary School in Salatiga. This qualitative research covers only three of them taken as purposive sampling. Data collection was conducted through in depth interview, observation, and documentation. The results shows that the competence of Islamic Elementary School Teachers in Salatiga hasnot done the mastery of learning based on technology, observation and development. This can cause low employee motivation, lack of learning facilities, the work ethic are still low, academic supervision, and socioeconomic conditions. Low-impact in the competence of professional teachers is caused by non optimal learning, ineffective and inefficient learning, less comfortableand enjoyable learning, less innovative, dynamic and productive learning results